Prioritizing preferred traits in the yam value chain in Nigeria: a gender situation analysis - Okoye, Benjamin; Ofoeze, Miriam; Ejechi, Mercy; Onwuka, Samuel; Nwafor, Solomon; Onyemauwa, Nnaemeka; Ukeje, Blessing; Eluagu, Chinwe; Obidiegwu, Jude; Olaosebikan, Olamide; Madu, Tessy (Frontiers in Sociology, 2023)
The study describes what worked and what didn't behind the prioritization of preferred traits within the yam and food products (boiled and pounded) value chain in Nigeria. Demand-led breeding protocols have enhanced participatory methods along gender lines, to increase clarity of information regarding the yam traits preferred by farmers and other end users. With the experiences of the crosscutting gender team at the National Root Crops Research Institute (NRCRI), Umudike, and partners, this study documents the successes and constraints in the use of gender-inclusive approaches for effective breeding. Methods in our gender studies involve critical assessment of the distinction between quantitative and qualitative research with particular attention to measurement. Various techniques of data collection, such as interviews, observation and archival studies are assessed to locate their potential for constructing successful research projects. Methods used include participatory varietal selection (PVS), participatory plant breeding (PPB), focused discussions with farmer groups, value chain mapping, G+ tools, trait preferences (processing and consumption), triangulation of multi-disciplinary dataset, and social survey research. Yam production in South-East Nigeria is dominated by men, while women are the main processors. Gendered power play, access to resources, and decision-making constrained women's participation in yam production (and in yam research). Sex disaggregation was applied within the value chain studies to capture the complementarity and differences in the perceptions of women and men. The methods used facilitated the development and release of three improved yam varieties to farmers in 2023 with consumer-preferred characteristics such as high yield, high dry matter, white tubers, and good boiling and pounding capability. The success stories also show that effective communication, and cooperation within the gender cross-cutting team and farmer groups are important for better results. When gender specialists, food scientists and breeders work together, innovations are created, challenges are overcome and information is shared.